2013
DOI: 10.4028/www.scientific.net/kem.594-595.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thickness for Sound Absorption of High Density Biopolymer Foams

Abstract: Waste cooking oils are problematic disposal especially in the developed countries. In this paper, waste cooking oil is used as raw material to produce foam. The purpose of the study is to develop the high density solid biopolymer (HDB) by using hot compression moulding technique based on flexible and rigid crosslinking agents. Physical properties such as Scanning Electron Microscope (SEM) and density of HDB were examined. The acoustic study of HDB for flexible and rigid has been measured using impedance tube t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many studies found that the density factor will affect the acoustic performance on both sound absorption and transmission loss. Research by Wang and Torng [23] and Latief, et al found the increment of density could increase the sound absorption coefficient in low frequencies [24]. Different results were released in research by Nandanwar, et al where low density fiber boards possess a higher sound absorption coefficient than high density fiber boards [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies found that the density factor will affect the acoustic performance on both sound absorption and transmission loss. Research by Wang and Torng [23] and Latief, et al found the increment of density could increase the sound absorption coefficient in low frequencies [24]. Different results were released in research by Nandanwar, et al where low density fiber boards possess a higher sound absorption coefficient than high density fiber boards [25].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies found that the density factor will affect the acoustic performance on both sound absorption and sound transmission loss. Acoustical response of wool board was reported by Hua and Enhui (2017) [22], while glass fiber and rockwool materials and high desinty bio-polymer foam (HDBP) were reported by Wang and Trong (2001) [23] and Latief et al (2014) [24] respectively. Another research by Nandanwar et al (2017) [25] showed that lower density fiber board posed a better sound absorption performance compared to similar board with a higher density.…”
Section: Introductionmentioning
confidence: 99%
“…The porosity of BF is higher as compared to CB due to the high porosity in the samples: 0.014 and 0.0043, respectively. This is due to the fact that the materials produced from particle structure gave higher density than the materials produced from cellular structure [18].…”
Section: Densitymentioning
confidence: 99%
“…One hundred and sixty grams of biopolymer foam was weighed and filled in the mould cavity with internal core size of 180 × 180 × 15 mm in order to decrease the thickness and pore size by using hot compression moulding. The parameter of the hot compression machine was set at 90 ∘ C of temperature, under 26 tonnes of pressure within 1 hour [18][19][20][21][22]. The compress biopolymer (CB) samples and compress biopolymer composite (CBC) were further prepared into 50 mm × 50 mm × 10 mm block.…”
Section: Preparation Of Samplesmentioning
confidence: 99%